Assessment of the Impact of Higher Temperatures Due to Climate Change on the Mortality Risk Indexes in Ecuador Until 2070 - Montenegro, M.; Campozano, L.; Urdiales-Flores, D.; Maisincho, L.; Serrano-Vincenti, S.; Borbor-Cordova, M. J. (Frontiers in Earth Science, 2022)
Extreme weather conditions, including intense heat stress due to higher temperatures, could trigger an increase in the mortality risk. One way to evaluate the increase of mortality risk due to higher temperatures is the High Risk Warming (HRW), which evaluates difference between the future and base period of a given percentile of daily maximum temperature (Tmax). Another is to calculate the future increase on the number of days over the temperature of such percentile. Previous studies point to the 84th percentile of the optimum temperature. Thus, this study aims to evaluate HRW and HRD in Ecuador, from 2011 to 2070 over the three natural climates zones e.g. Coast, Andes and Amazon. This climate analysis is based on historical meteorological stations, and projections from CSIRO-MK36, GISS-E2 and IPSL-CM5A-MR, CMIP5 global climate models. The Representative Concentration Pathways (RCP), 8.5, were considered, which are related to the highest increases in future temperature. The results indicate that HRW and HRD will experience a larger increase in the period 2041-2070 compared with the period 1980-2005; in particular, these two indices will have a progressively increasing trend from 2010 onwards. Specifically, the HRW calculated from the CMIP5 models for all stations is expected to grow from 0.6° C to 1.4°C and from 1.8°C to 4.6 °C for 2040 and 2070, respectively. Also, it is expected that the HRD for all stations increases from 42 to 74 and 120 to 227 warming days for 2040 and 2070, respectively. The trends derived using Sen´s slope test show an increase of the HRW between 0.5 ° to 0.9 °C/decade and of the HRD around 2.88 to 4.9 day/decade since 1985. These results imply a high increase of heat related mortality risks related to climate change in Ecuador. In terms of spatial distribution, the three Ecuadorian regions experienced more critical temperatures conditions, with higher values of HRW and HRD for 2070. As a response to the increased frequency trends of hot periods in tropical areas, urgent measures should be taken to review public policies and legislation to mitigate the impacts of heat as a risk for health in Ecuador.